Identification and characterization of Botrytis cinerea causing gray mold on tomato in Malaysia - Yusoff, Siti Fairuz; Ismail, Siti Izera; Haron, Farah Farhanah; Shafari, Zahir Shah; Hashim, Rohasmizah; Paiman (Malaysian Applied Biology, 2024)
Botrytis cinerea, commonly known as gray mold, is a pervasive fungal pathogen that affects a wide range of plant species, leading to significant agricultural losses. The identification of Botrytis cinerea in Malaysia is crucial for protecting the agricultural sector, minimizing economic losses, ensuring food security, maintaining export quality, addressing environmental concerns, and advancing scientific research. In the present research, tomato fruits collected from Cameron Highlands, Pahang, Malaysia showed gray mold disease symptoms of B. cinerea. The fungal isolates were examined morphologically for colony colour, growth rate, conidiophores, conidia shape, and sclerotia on PDA and V8 agar. According to the results, conidiophores appeared in grape shape and length was range of 21.26-32.52 μm, ovoid conidial dimensions were in the range of 10.03-16.08 × 7.37-11.15 μm and sclerotia size was range 1.91-4.50 × 1.70-4.00 mm. All isolates were attributed to the morphospecies Botrytis cinerea on account of these characteristics. The resulting sequences deposited in GenBank were accessions MT012053 to MT012062, respectively. A BLAST analysis of the resulting 550-bp nucleotide sequences showed 99-100% identity closest matched to B. cinerea. The pathogenicity experiments showed P6 isolates of B. cinerea were highly pathogenic and caused gray mold development on tomato fruits that led to severe symptoms in five days. Meanwhile, the least pathogenic isolate was P9. In terms of temperature, B. cinerea grew faster on PDA at 20ºC, slower grew below 20ºC and did not grow at 25ºC. Identification and characterization of B. cinerea on tomato could potentially provide information to assist disease management strategies for B. cinerea.